2003
DOI: 10.1159/000072306
|View full text |Cite
|
Sign up to set email alerts
|

Differential Changes in Dopamine D<sub>2</sub>- and D<sub>1</sub>-Receptor mRNA Levels Induced by Hypoxia in the Arterial Chemoreflex Pathway Organs in One-Day-Old and Adult Rabbits

Abstract: This study determined: (1) whether dopamine (DA) D2-receptor (R) and D1-R mRNA levels in the carotid body (CB), petrosal ganglion (PG) and superior cervical ganglion (SCG) are modulated by hypoxia; (2) the role of hypoxia intensity and exposure duration, and (3) whether the pattern of modulation differs between newborn (1-day-old) and adult rabbits. Rabbits were exposed to five FiO2 conditions: 21% (control); 15%/6 h; 15%/24 h; 8%/6 h and 8%/24 h. D2- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…The immunoreactivity for HCN2 is of interest because HCN2 is modulated by cAMP. Transmitters such as dopamine which is released from the glomus cells may alter cAMP levels in the terminals via postsynaptic D1/D2 receptors (Bairam et al 2003; Czyzyk-Krzeska, 1992; Kline et al, 2002) and thus regulate the terminal membrane potential through HCN2. This is in line with the modulatory role of dopamine proposed in a recent review (Iturriaga and Alcayaga, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The immunoreactivity for HCN2 is of interest because HCN2 is modulated by cAMP. Transmitters such as dopamine which is released from the glomus cells may alter cAMP levels in the terminals via postsynaptic D1/D2 receptors (Bairam et al 2003; Czyzyk-Krzeska, 1992; Kline et al, 2002) and thus regulate the terminal membrane potential through HCN2. This is in line with the modulatory role of dopamine proposed in a recent review (Iturriaga and Alcayaga, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, newborn rabbits exposed to 8% O 2 for 24 hours immediately after birth show a decrease in dopamine D 2 receptors mRNA expression in comparison to the levels measured in normoxic pups (Fig. 3) [59]. Together, these observations clearly indicate that exposing carotid bodies to excessive or insufficient O 2 -related stimulation causes significant alterations in carotid body oxygen sensitivity and that changes in dopaminergic neurotransmission contribute (at least in part) to the functional phenotype subsequently observed in these animals.…”
Section: A) Chronic Exposure To Hypoxia or Hyperoxiamentioning
confidence: 73%
“…In contrast, hypoxia profoundly increased DRD2 mRNA in the rostral nucleus tractus solitarius at all time points investigated [17]. A study conducted on rabbit brains also revealed that hypoxic expression patterns of DRD1 and DRD2 in different brain areas are far from being uniform [18]. Moreover, widely accepted concepts like induction of the tyrosine hydroxylase gene by hypoxia [19] have been challenged by recent studies finding practically unaltered or slightly decreased transcript and protein levels upon hypoxia [20,21].…”
Section: Introductionmentioning
confidence: 99%